Geology, Geochemistry and Geotectonic Setting of the Pan-African Granites and Charnockites Around Ado-Ekiti, Southwestern Nigeria - Oyinloyea, Akindele O.; Obasi, Romanus (Biological Sciences - PJSIR, 2006)
The geology, petrology and geochemistry of the coarse-grained and fine-medium-grained gneissic charnockites and the porphyritic biotite-hornblende and medium-grained older granites in the Ado-Ekiti area were studied. Xenoliths of schistose quartzite occur within these charnockitic and granitic rocks. The porphyritic older granite and the coarse- grained charnockite occur in very close association in the field. All these rocks contain monazite, in their mineralogical composition, which indicate crustal input into their original magma. Aluminium-total iron-magnesium (AFM) plot for these rocks indicated that they were calc-alkaline in nature and were formed in a subduction related tectonic setting. Percentage normative corundum versus mol. A12O3/(Na2+K2O+CaO) plots for the older granites and the charnockites from the Ado-Ekiti area revealed that their original magma was derived from a mixed source (igneous and crustal). Y+Nb versus Rb plots for the older rare earth granites and the charnockites indicated that they originated from a volcanic arc and within-plate environments. The normalised rare earth elements (REE) patterns showed that these rocks were genetically related, and the feldspar fractionation took place during their formation as revealed by Eu depletion patterns in the REE diagrams. The negative Eu/Eu* (ratio of absolute europium to normalized europium) anomaly and (La/Yb)N ratios higher than 5 obtained in these rocks indicated that they were emplaced through magmatic fractionation. The mixed magma from which these rocks were derived was formed in a back arc tectonic setting where an ocean slab was subducted into the mantle leading to the generation of magma, which intruded into the earlier formed rocks in a back arc basin. The charno- ckites and the older granites were the end products of the differentiation of such magma.